Unusual Foreign Body in Nasal Cavity : A Case Report - Santanu Shit; Ashim Sarkar; Tshering Dorjee Sherpa; Ritam Ray; Manoj Mukherjee; Manotosh Dutta (Bengal Journal of Otolaryngology and Head Neck Surgery, 2013)
The foreign bodies of the nasal cavity are commonly seen in the pediatric population.Adult with nasal foreign bodies are rare. Whenever the adult patients present with nasal foreign bodies, the underlying psychiatric disorder must be searched for. Patients with normal intelligence may also present with foreign bodies inside nasal cavity. Self introduction of foreign bodies inside nasal cavity and self destructive behaviors are rare.Wepresent here a unique case of foreign body inside nasal cavity which was accidentally discovered preoperatively.